(untitled) (Journal of Economic Research & Business Administration, 2018)
This scientific article is devoted to the study of the specifics of the formation and features of the development of national models of market economies. The article provides in-depth theoretical and methodological approaches to the conceptual apparatus associated with the country (national) model, the structuring of national models of market economies, the distinctive features of types of market models, the description of a socially-oriented model of a market economy and the features of the formation of a market economy in the Republic of Kazakhstan. Models of market economies have unique country features that determine the nature of their functioning and development. The economic model of each country is, first of all, an intellectual structure that acts as a result of a long historical process during which a correlation of the elements of the model is built up and the mechanism of their interaction in the economic sphere is formed. Proceeding from this, the mechanical borrowing of the national economic system and its achievements for another country is impossible. A comparative analysis of national models of the economy existing in the world economy taking into account their evolutionary development is usually carried out on the basis of criteria, the result of which are proposals for the typologization of national models. Conclusions and recommendations can be used in the activities of state bodies both in the center and in the field.